Transcutaneous auricular vagus nerve stimulation alleviates anxiety-like behaviors in mice with post-traumatic stress disorder by regulating glutamatergic neurons in the anterior cingulate cortex - Zhijun Diao; Yan Zuo; Jinming Zhang; Ke Chen; Yongbin Liu; Yuwei Wu; Feng Miao; Haifa Qiao (Translational Psychiatry)
Abstract Vagus nerve stimulation has been certified to be an effective therapeutic modality for emotional disorders, especially anxiety triggered by post-traumatic stress disorder (PTSD). Nevertheless, the neural mechanisms underlying the efficacy of transcutaneous auricular vagus nerve stimulation (taVNS) remain poorly understood. In this study, we aimed to elucidate whether and how taVNS influences anxiety-like behaviors elicited by PTSD, focusing on synaptic plasticity in taVNS-activated neurons (TANs) of the anterior cingulate cortex (ACC). Our findings substantiate that taVNS significantly mitigates anxiety-like behaviors in PTSD-like male mice via activating specific glutamatergic neurons in the ACC. Notably, these glutamatergic TANsACC exhibited marked enhancements in presynaptic excitatory transmission relative to those non-activated glutamatergic neurons in the ACC. This enhancement of presynaptic release further prevented the induction of presynaptic long-term potentiation (pre-LTP), manifesting as presynaptic depotentiation. Furthermore, inhibiting these glutamatergic TANsACC weakened the positive effects of taVNS on anxiety-like behaviors in PTSD-like male mice. Conversely, activating these glutamatergic TANsACC did not further amplify the effects of taVNS on anxiety-like behaviors. Collectively, our results reveal that the upregulation of presynaptic transmission in glutamatergic TANsACC is responsible for the positive effects of taVNS on anxiety-like behaviors in PTSD-like male mice, providing new insights into functional and activity patterns of the specific brain regions involved in the effects of taVNS.